Harvest index and biological yield for comparison of soybean cultivars efficiency - Colasante, Luiz Osvaldo; Costa, José Antonio (Pesquisa Agropecuaria Brasileira, 2014)
A field trial was conducted during the 1978/79 growing season to investigate the variability for harvest index and biological yield of twenty soybean cultivars from several maturity groups. Interrelationships between grain yield and other agronomic characteristics were also looked for. Medium and late maturity cultivars showed the highest values for grain yield, biological yield and plant height. Variability was found for harvest index and biological yield among cultivars, regardless of the maturity group. Harvest index varied from 43.2% to 50.2% and although most of the late maturity varieties have shown lower harvest index than the early maturity varieties an inverse relation between them was not always present. The main factor determining grain yield differences among cultivars was the variation In their biological yields, although high grain yields could be obtained by different combinations between harvest index and biological yield. Harvest index was not correlated with grain yield, but biological yield was a good indicator of yield potential of soybean cultivars.